Purchasing Decision for Crystal Guava Fruit: Influence of Product Attributes, Attitudes, and Consumer Interest - Hendro Priyo Tri Utomo; Abdul Wahib Muhaimin; Riyanti Isaskar (The University of Lampung, 2025)
Crystal guava (Psidium guajava L.) holds significant growth potential in Indonesia due to its large fruit size, immaculate flesh, minimal seed content (less than 3%), and high vitamin C levels. However, production faces challenges such as inconsistencies in quality and freshness, variations in fruit shape that deviate from market preferences, and inconsistent quality among farmers in Bojonegoro Regency. This study investigates the impact of product attributes, customer attitudes, and consumer interest on purchasing decisions for crystal guava in the region. A descriptive quantitative approach was employed, utilizing Structural Equation Modeling (SEM) with Warp Partial Least Square (WarpPLS). Primary data were gathered through structured questionnaires with 117 respondents, while secondary data were obtained from literature reviews using a non-probability sampling method. The results reveal that product attributes positively influence customer attitudes and consumer interest. Additionally, consumer interest and attitudes significantly affect purchasing decisions. The study underscores the importance of improving product quality and consistency to enhance customer perceptions and interest. Addressing these issues will not only meet consumer expectations but also boost market demand for crystal guava in Bojonegoro Regency. Strengthening product attributes is critical to fostering favorable attitudes, increasing interest, and driving purchasing decisions. Keywords: Consumer attitudes, Consumer interests, Crystal guava fruit, Product attributes, Purchase decisions.